2008
DOI: 10.1007/s00128-008-9440-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antioxidant Circulatory Lipid-Soluble Vitamins and Sodium as Non-invasive Indicators of Chronic Copper Exposure and Toxicity in Rainbow Trout, Oncorhynchus mykiss

Abstract: Measurement of circulatory indicators of copper (Cu) exposure and toxicity in rainbow trout revealed elevated Cu concurrent with reduced sodium (Na) concentrations in plasma of Cu-exposed fish. Using a new normal phase high performance liquid chromatography (HPLC) method developed and validated for simultaneous extraction of lipid-soluble antioxidant vitamins we found that, contrary to our original hypothesis, plasma antioxidant status was enhanced as evidenced by a linear increase in vitamin E concentration. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This finding is supported by the significant positive relationships between retinol and retinyl palmitate with lipid peroxidation (measured as malondialdehyde, Table 2). In an experiment with rainbow trout exposed to Cu, Kamunde et al [30] also observed enhancement of the antioxidant status (in their case, vitamin E) with a prooxidant metal (Cu) in plasma.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This finding is supported by the significant positive relationships between retinol and retinyl palmitate with lipid peroxidation (measured as malondialdehyde, Table 2). In an experiment with rainbow trout exposed to Cu, Kamunde et al [30] also observed enhancement of the antioxidant status (in their case, vitamin E) with a prooxidant metal (Cu) in plasma.…”
Section: Discussionmentioning
confidence: 96%
“…Although these lagoons were initially selected to be reference lagoons, previous studies have shown that they may have been affected by anthropogenic sources of trace elements, probably from atmospheric deposition [20]. In order to sample the main components of the fish community in the lagoons, samples were collected using gill nets of various mesh sizes (20,25,30,40, and 50 mm). Fish were killed by a blow to the head, wrapped in aluminum foil, transported on ice to the lab, and preserved frozen (À208C) for one week.…”
Section: Study Area and Sample Collectionmentioning
confidence: 99%